1948
DOI: 10.1021/ie50460a029
|View full text |Cite
|
Sign up to set email alerts
|

Residual Action of Organic Insecticides

Abstract: The residual action of nonvolatile organic insecticides is governed largely by their resistance to chemical change under field conditions.Oxidation has been shown to be a common cause of failure in pyrethrum, rotenone, phenothiazine, and DDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1951
1951
1968
1968

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Decomposition, once started, continued even after the benzene had evaporated. Fleck (1948) confirmed these findings, and showed that the rate of decomposition of DDT in solution under the influence of ultra-violet light depended on the type of solvent. He also showed (Fleck, 1949) that decomposition by ultra-violet light gave a different product depending on whether air was present or absent, and that dehydrochlorination was not necessarily the first step involved.…”
Section: Department Ofsupporting
confidence: 66%
“…Decomposition, once started, continued even after the benzene had evaporated. Fleck (1948) confirmed these findings, and showed that the rate of decomposition of DDT in solution under the influence of ultra-violet light depended on the type of solvent. He also showed (Fleck, 1949) that decomposition by ultra-violet light gave a different product depending on whether air was present or absent, and that dehydrochlorination was not necessarily the first step involved.…”
Section: Department Ofsupporting
confidence: 66%
“…The insecticide that enters the plant parts is not easily recognizable after it is released by the plant. Thus, to determine the residual action of an insecticide there is need to study its vapor pressure, sticking power, solubility, and absorption into the surface on which it is applied, as well as resistance to chemical change (4).…”
Section: Residual Action Op Pesticidesmentioning
confidence: 99%
“…(a). Although it is decomposed by air in the presence of light or alkalis (Fleck, 1948), rotenone is not specially reactive and can be absorbed by bean leaves and carried to other parts of the plant, apparently unchanged (Fulton & Mason, 1937). D D T is rapidly decomposed by bases, but is otherwise stable.…”
Section: Physical Drug Actionmentioning
confidence: 99%